Forecast combinations in a DSGE-VAR lab - Mauro Costantini; Ulrich Gunter; Robert M. Kunst (Institute for Advanced Studies (IHS), 2014)
We explore the benefits of forecast combinations based on forecast- encompassing tests compared to simple averages and to Bates-Granger combinations. We also consider a new combination method that fuses test-based and Bates-Granger weighting. For a realistic simulation design, we generate multivariate time-series samples from a macroe- conomic DSGE-VAR model. Results generally support Bates-Granger over uniform weighting, whereas benefits of test-based weights depend on the sample size and on the prediction horizon. In a corresponding application to real-world data, simple averaging performs best. Uni- form averages may be the weighting scheme that is most robust to empirically observed irregularities.
Keywords: 330; combining forecasts; encompassing tests; model selection; time series; DSGE-VAR model